ZAKRES POJĘCIA „PRZEDSIĘBIORCA” W PRAWIE DZIAŁALNOŚCI GOSPODARCZEJ ORAZ W INNYCH AKTACH PRAWNYCH - Lissoń, Piotr (Wydział Prawa i Administracji UAM, 2002)
The aim of the article is to present the notion of entrepreneur both in the light of the Business Activity Law Act of the 19th November 1999 and in other legal acts, arriving at conclusions drawn from the current state of affairs. The author makes an assumption that this notion is among the most crucial ones in the area of legal regulation of business relationships and it should as such be used by the legislator in the legal system in a standardised manner, so that the term universally denotes only one single meaning. The author postulates that the meaning of the term „entrepreneur” should be consistent with the definition presented in the Business Activity Law Act, which has a special system-making character, as it regulates the general issue of undertaking and conducting business activities. In order to attain the goal of this article, the author poses the following questions that determine the order of the article: what is the genesis of the term „entrepreneur” in the Polish law? What is the meaning o f the term in the light of the Business Activity Law Act? Has the legislator introduced any changes to the meaning of the term since the publication of the Act? And finally, in what way do separate legal acts deal with this notion, or in what acts is it mentioned and what meaning does it have in those texts? Since the article is set within the general topic of „Business activity law one year after its introduction”, the considerations presented in this article are ordered chronologically. The author makes an attempt to juxtapose various changes in the meaning of the term „entrepreneur” over time, trying to systematise them and assess from the legislative technique principle perspective, i.e. regarding the principles of drawing up correct legal acts. On the basis of the accepted criteria, the author draws conclusions from the current state of affairs in the law. These conclusions are twofold. Firstly, some are critical of the construction of the „entrepreneur” notion in the Business Activity Law Act and other legal acts. The author blames the legislator for lack of transparency in constructing legal regulations and incoherence in the legal solutions applied, which is especially visible in the variety of different definitions of this term in numerous legal acts. Secondly, the author postulates some changes in the legal provisions in order to do away with the existing irregularities.
NOTION OF ENTREPRENEUR IN BUSINESS ACTIVITY LAW ACT AND IN OTHER LEGAL ACTS